2020
DOI: 10.3324/haematol.2020.247973
|View full text |Cite
|
Sign up to set email alerts
|

Philadelphia-like acute lymphoblastic leukemia is associated with minimal residual disease persistence and poor outcome. First report of the minimal residual disease-oriented GIMEMA LAL1913

Abstract: Philadelphia-like acute lymphoblastic leukemia is associated with minimal residual disease persistence and poor outcome. First report of the minimal residual disease-oriented GIMEMA LAL1913

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 37 publications
2
56
0
Order By: Relevance
“…[66] [Figure 1]. A similar trend has been found in B-ALL specifically, with the highest incidence seen in Hispanics/Latinos and the lowest in Blacks [94] . Among older adults, ALL incidence again predominates among Hispanics/Latinos [5] .…”
Section: Incidence Of All Is Highest In Hispanics/latinossupporting
confidence: 66%
“…[66] [Figure 1]. A similar trend has been found in B-ALL specifically, with the highest incidence seen in Hispanics/Latinos and the lowest in Blacks [94] . Among older adults, ALL incidence again predominates among Hispanics/Latinos [5] .…”
Section: Incidence Of All Is Highest In Hispanics/latinossupporting
confidence: 66%
“…A 44‐year‐old man diagnosed in March 2018 with early T‐precursor ALL was treated according to an intensive paediatric‐like protocol, 9 achieving complete remission (CR) but not MRD‐negative status. After total body irradiation‐based myeloablative allo‐SCT from his haploidentical sister, bone marrow (BM) MRD became negative, but reappeared three months later.…”
Section: Figurementioning
confidence: 99%
“…This study reported 100% complete remissions even for Ph-like ALL, although with a short duration, lower number of molecular remissions and a higher rate of early relapses, confirming the negative prognostic impact on survival of the Ph-like ALL subtype in intensively treated older adults [ 17 ]. A similar prevalence (~20%) and poor clinical outcome were observed in patients enrolled in different GIMEMA (Gruppo Italiano Malattie EMatologiche dell’Adulto) clinical trials [ 18 ], where patients with Ph-like ALL had a lower rate of complete remissions and a worse event free survival compared with non Ph-like ALL cases [ 18 , 19 ].…”
Section: Clinical Features Of Ph-like Allmentioning
confidence: 74%